IMPLEMENTASI NILAI MODERASI BERAGAMA DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MAN 1 DARUSSALAM CIAMIS - Mohamad Jaenudin; Saca Suhendi; Hasbiyallah Hasbiyallah; Tatang Muh Nasir (Kuttab : Jurnal Ilmu Pendidikan Islam, 2023)
The lack of reinforcement of madrasah education causes the flexibility of religious and social values possessed by students, namely the development of extreme ways of thinking and behaving in religion that ignore human values, resulting in problems of intolerance and divisions between religious communities, then there is fanaticism or the development of claims the subjective truth of religious interpretation by rejecting differences and claiming that only one's opinion is right, the others are wrong, whereas what we have to understand is that the different colors of understanding should be a common good. This study aims to explain the Implementation of Religious Moderation Values in learning Islamic Cultural History (SKI) at MAN 1 Darussalam Ciamis. This type of research uses field qualitative with descriptive analysis method, while the data sources of this research consist of madrasa heads, teachers and students with data collection tools including interviews, documentation and observation. The results of the study show that the implementation of religious moderation in Islamic Cultural History (SKI) learning has a very good impact on the formation of student character which is able to reflect an attitude of religious moderation through moderate, fair, tasamuh and ta'awun Islamic cultural learning activities which are reflected in students' attitudes.